POTRET PELAKU USAHA TANI JAGUNG DAN UBI JALAR DI MASA PANDEMI (Studi Kasus di Kelompok Tani Mukti, Desa Sukajadi, Kabupaten Bogor) - Muhammad, Hilmi; Judawinata, M. Gunardi (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Sukajadi Village has the most extensive agricultural land compared to other villages that has high agricultural potential compared to other villages. However, the average farmer still uses conventional farming systems. This can be overcome a little by the existence of farmer groups. However, due to the Covid-19 pandemic, the prices of agricultural products such as corn and sweet potatoes have decreased. As a result, several markets in Bogor Regency experienced unstable prices. The purpose of this study is to describe the actors of maize and sweet potato farmers, to describe how the Mukti Farmers Group cultivates corn and sweet potato farming based on technical, economic, and social aspects in Sukajadi Village. Identify the profit level of corn and sweet potato farming during the pandemic. A qualitative-quantitative approach through case studies is used in this study. The conclusion of this study is that farmers in Sukajadi Village are dominated by tenant farmers who still tend to be productive, but in terms of land area they cultivate, they are small farmers with lower secondary education status, so they are indicated as traditional farmers. The technique of cultivating corn and sweet potatoes in Sukajadi Village tends to be traditional. Marketing of farmers' products in Sukajadi Village tends to be traditional because farmers' prices can be cheaper. Based on the analysis of farming in Sukajadi Village, R/C > 1 was obtained, so that farming was included in the profitable category.